2018
DOI: 10.1002/jcp.26290
|View full text |Cite
|
Sign up to set email alerts
|

Roles and clinical implications of microRNAs in acute lymphoblastic leukemia

Abstract: MicroRNAs (miRNAs) are a class of small noncoding RNAs which regulate the expression of target genes by binding to messenger RNAs. miRNAs play a role in various biological processes, including proliferation, apoptosis, and tumorigenesis. Dysregulation of miRNAs is implicated in invasion and metastasis in several human cancer types, and leukemia is not an exception. Acute lymphoblastic leukemia (ALL) is a hematological malignancy characterized by the proliferation of early lymphoid precursors that replace norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 120 publications
0
31
0
Order By: Relevance
“…In 75% of cases, ALL originate from precursors of the B-cell lineage; the remaining cases consist of malignant T-cell precursors [48]. The expression profiling of miRNAs in ALL could be used for the classification, setting specific diagnoses, and proposing the prognostic importance of ALL in the future [49]. Jin J et al investigated the expression and possible targets of miR-144 in ALL patients.…”
Section: Mir-144 In Acute Lymphoblastic Leukemiamentioning
confidence: 99%
“…In 75% of cases, ALL originate from precursors of the B-cell lineage; the remaining cases consist of malignant T-cell precursors [48]. The expression profiling of miRNAs in ALL could be used for the classification, setting specific diagnoses, and proposing the prognostic importance of ALL in the future [49]. Jin J et al investigated the expression and possible targets of miR-144 in ALL patients.…”
Section: Mir-144 In Acute Lymphoblastic Leukemiamentioning
confidence: 99%
“…These micro markers have proven to be very promising chALL biomarkers and have widespread clinical applications because of their stability and resistance to degradation in not only blood, but also various biological specimens (such as tissue, sputum, stool and formalin-fixed paraffin-embedded (FFPE) specimens), easily measured, and most importantly, their quantities correlates with the presence of the malignancy or with clinically relevant malignancy features (8,14,(95)(96)(97). Recent studies have revealed that extracellular circulating miRNA levels in secreted membrane vesicles (microvesicles and exosomes), blood serum, and other body fluids can be used as biomarkers to diagnose, classify and predict prognosis of chALL (96,(98)(99)(100)(101). miRNA expression dysregulation in cancers is because of different mechanisms, such as deletion or amplification of miRNA related genes, abnormal transcriptional control of miRNAs, epigenetic dysregulation and defects in the biogenesis machinery of miRNA (102).…”
Section: Mirna Levels Alterationmentioning
confidence: 99%
“…Due to the promising characteristics of high stability, low cost, possibility of repeated sampling and noninvasiveness, circulating biomarkers have received extensive attention in molecular medicine nowadays. Compelling evidences have shown that these types of biomarkers are measurable in secreted membrane vesicles (microvesicles and exosomes), blood serum, and other body fluids and can be used as biomarkers to diagnose, classify, follow-up and predict prognosis in chALL (96,(98)(99)(100)(101). It has been suggested that extracellular circulating biomarkers play an important role in intracellular communication in both paracrine and endocrine manners (101).…”
Section: Circulating Biomarkersmentioning
confidence: 99%
“…Left-right asymmetry during neuronal development, cardiogenesis, and fluid balance are some of the biological functions in which they are actively involved [20][21][22]. Alterations in miRNA pathways have been implicated in a variety of human cancers and in infectious and noninfectious diseases, including autoimmune diseases, metabolic disorders, and genetic diseases [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%